DESAIN PELETAKAN PENYANGGA DAN EVALUASI TEGANGAN PADA SISTEM PERPIPAAN FLUIDA MASSECUITE DARI REHEATER MENUJU FEED MIXER - Pekik Mahardhika (P3M Politeknik Negeri Indramayu, 2020)
The sugar industry is a very important industry in Indonesia to meet the needs of the domestic market. One of the products of the sugar company is white crystal sugar. In the process of producing white sugar there is a fluid called Massecuite. Massecuite is a mixture of fluid crystals of sugar and water. Massecuite can cause sedimentations and blockages in the pipeline from the heater to the feed mixer. The line pipe from the reheater to the feed mixer has been redesigned. But the line pipe has not been designed for laying penyangga and evaluate piping stress. So that the line pipe needs to be designed for laying penyangga and evaluate piping stress. Evaluation of piping stress accordance to ASME B31.3 Process Piping. This evaluation aims to ensure that the line pipe design comply with ASME B31.3 requirements. The evaluation results evidence that the stress in the line pipe from the reheater to the feed mixer still meets the ASME B31.3 criteria. The line pipe design from the reheater to the feed mixer can be declared safe.